Responsibilities of Financial Technology Company Due To Failure to Pay By Loan Recipients - Janisriwati, Sylvia (Jambura Law Review, 2021)
One form of business is due to current developments in financial technology (abbreviated as fintech), which means using technology to provide financial solutions. This study aims to see the responsibility of PT. Dana Agung Nusantara as the financial technology (fintech) lending provider due to default by lending recipients in the case of Central Jakarta Commercial Court Decision Number 113/Pdt.Sus-PKPU/2021/PN Jkt.Pst. This research is normative juridical research. In this study, the source of legal materials used consisted of 3 (three) legal materials, namely primary, secondary and tertiary legal materials. The technique of collecting data on legal materials is by using a literature study model using analysis of legal materials, which is used in descriptive qualitative content analysis. The results showed that the responsibility of PT. Dana Agung Nusantara as the financial technology (fintech) lending provider due to default by loan recipients by the case of Central Jakarta Commercial Court Decision Number 113/Pdt.Sus- PKPU/2021/PN Jkt.Pst that according to an OJK spokesperson, the party is responsible if The fintech collapsed is a P2P lending fintech provider. Meanwhile, if the borrower causes a default, it is the responsibility of the lender or investor.